2022
DOI: 10.3390/ani12212974
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Garlic and Ginger Oil to Reduce Salmonella in Post-Harvest Poultry

Abstract: Approximately 1.35 million human salmonellosis cases are reported in the United States every year, resulting in over 26,000 hospitalizations and 400 deaths. Consumption of contaminated poultry products is one of the leading causes of human salmonellosis. Poultry meat becomes contaminated when feces from an infected bird comes into contact with the carcass during processing. Additional carcasses can then become cross-contaminated along the processing line. While chemicals such as peracetic acid are currently us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Indeed, a previous study had focused on the potent antibacterial aspects of garlic and ginger against both Salmonella and S. aureus strains ( Chand, 2013 ). Other studies carried out in Egypt ( Elmowalid et al, 2019 ) and USA ( Robinson et al, 2022 ) confirmed that garlic and ginger had effective antibacterial properties against S. aureus and Salmonella strains. Like the findings of the current study, the considerable antibacterial activity of cinnamon EO had been proved against S .…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, a previous study had focused on the potent antibacterial aspects of garlic and ginger against both Salmonella and S. aureus strains ( Chand, 2013 ). Other studies carried out in Egypt ( Elmowalid et al, 2019 ) and USA ( Robinson et al, 2022 ) confirmed that garlic and ginger had effective antibacterial properties against S. aureus and Salmonella strains. Like the findings of the current study, the considerable antibacterial activity of cinnamon EO had been proved against S .…”
Section: Discussionmentioning
confidence: 74%
“…Several other plant extracts have been shown to have effective Salmonella -reducing effects. Robinson et al described a reduction in Salmonella of up to two log CFU (99%) when Salmonella -infected chicken meat was dipped in garlic and ginger oil [ 47 ]. Nair et al demonstrated a pronounced bactericidal effect against Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%